Siphonoecetini Just, 1983 (Crustacea, Amphipoda, Ischyroceridae) 9: New species in Rhinoecetes Just, 1983, Cephaloecetes gen. nov. and Neoecetes gen. nov. from the south-eastern Australian shelf - Just, Jean (Zootaxa, 2012)
Six new species of Rhinoecetes Just, 1983, R. rhinoceros, R. dinoceros, R. brevirostris, R. coclearis, R. albomaculosus andR. meridianus, are described together with Cephaloecetes enigmaticus gen. nov., sp. nov. and Neoecetes conipes gen.nov., sp. nov. from eastern Australia from Moreton Bay in Queensland to Bass Strait and Tasmania. Cephaloecetes gen.nov. differs from Rhinoecetes by having the head front margin entire and a pseudorostrum arising underneath from thefrons. Neoecetes gen. nov. differs from Rhinoecetes in having two robust setae instead of one on the posterior projectionof gnathopod 2 carpus, a row of small accessory robust setae on pereopods 5 and 6 carpus instead of a single one, anduropod 3 ramus being conical instead of round. Keys to genera and species are given. A novel character, a pair of sternalpapillae, is documented in Rhinoecetes and Cephaloecetes on the ventral surface of pereonite 7 in adult females. The dis-tribution of the species is commented upon. The most diverse fauna of Siphonoecetini was found in Jervis Bay, New South Wales.